Development of the Creative Economy of the Village Karang Taruna Community Based on YouTubers and Microstokers - Fathoni, Tamrin; Muqorrobin, Syamsul (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The background to this work is that although 90% of Nglarangan village youth have access to smartphones and are involved in social media, most still face obstacles in finding work that suits their potential and interests. This service aims to revitalize the post-COVID-19 economy by empowering the young generation in Nglarangan Village, Kauman District, and Ponorogo Regency by creating YouTube content. This service method uses the Asset Based Community Development (ABCD) approach, which includes stages; identify assets, plan, and dream. Data collection techniques are done through interviews, observation, and documentation. The analysis technique compares the results of previous services with the same theme and with relevant theoretical studies. The result of this mentoring work is that this training not only opens up new job opportunities but also increases the income level in Nglarangan Village. By utilizing the digital landscape, Nglarangan Village is an example of an innovative economic revival after the pandemic. The younger generation's proficiency in using YouTube and the Microstoker platform generates economic prospects and fosters solidarity and creativity among Karang Taruna members. Apart from individual benefits, this initiative also positively impacts the village's image and contributes to local economic growth. Nglarangan Village is an inspiring model illustrating how creative economic empowerment, centered on digital platforms, can bring positive transformation after the challenges of the pandemic.